Diazepam Impairs Innate and Adaptive Immune Responses and Ameliorates Experimental Autoimmune Encephalomyelitis - Falcón, Cristian R.; Hurst, Nicolás Fernández; Vivinetto, Ana Laura; López, Pablo Héctor Horacio; Zurita, Adolfo; Gatti, Gerardo; Cervi, Laura; Monferran, Clara G.; Roth, German A. (Frontiers in Immunology, 2021)
Currently there is increasing attention on the modulatory effects of benzodiazepines on the immune system. Here, we evaluate how Diazepam (DZ) affects both innate and adaptive immunity. We observed that the treatment with DZ and Lipopolysaccharide (LPS) on macrophages or dendritic cells (DC) induced a defective secretion of IL-12, TNF-α, IL-6 and a lesser expression of classical activation markers as NO production and CD40 in comparison with LPS condition. More importantly, mice pre-treated with DZ and then challenged to LPS induced-septic shock showed a reduced death. The DZ treatment shifted the LPS-induced pro-inflammatory cytokine production of peritoneal cells (PC) to an anti-inflammatory profile commanded by IL-10. In agreement with this, DZ treatment prevented LPS-induced DC ability to initiate allogeneic Th1 and Th17 responses in vitro when compared with LPS matured DC. Since these inflammatory responses are key in the development of the Experimental autoimmune encephalomyelitis (EAE), we treated EAE-mice preventively with DZ. Mice that received DZ ameliorate clinical signs and immunological parameters of the disease. Additionally, DZ reduced the release of IFN-γ and IL-17 by splenocytes from untreated sick mice in vitro. For this reason, we decided to treat diseased mice therapeutically with DZ when they reached the clinical score 1. Most importantly, this treatment ameliorated clinical signs, reduced the MOG-specific inflammatory cytokine production and prevented axonal damage. Altogether, these results indicate that DZ is a potent immunomodulator capable to control undesired innate and adaptive immune responses, both at the beginning of these responses and also once they have started.